A adoção da perspectiva de gênero para efetivação do primado constitucional de equidade entre homens e mulheres no sistema de justiça criminal brasileiro, em especial para as mulheres vítimas de crimes contra a dignidade sexual - Pereira, Helaine da Silva Pimentel (2022)
The research analyzes the need to adopt a gender perspective for the realization of the constitutional principle of equity between men and women in the Brazilian criminal justice system, especially for women victims of crimes against sexual dignity, given the harmful influence of stereotypes and gender preconceptions about the legal arguments that support the reception of evidence in criminal proceedings related to such crimes, as it is an affront to their fundamental rights and guarantees. It starts from the hypothesis that the roles socially attributed to men and women, which historically privilege the former to the detriment of the latter, are reproduced at an institutional level, as a manifestation of structural male chauvinism. In this direction, it identifies, in legal doctrine and practice, signs that show the use of gender stereotypes and preconceptions, as well as analyzes whether these signs cause gender inequality in the criminal justice system, focusing on the approach given to the value of the word and the behavior of female victims. Then, it analyzes whether such signs are used as a discursive strategy for the maintenance of male power and, then, analyzes the need for legal action to be governed by the gender perspective, as an affirmative public policy for the realization of equity between men and women. The research adopts the dialectical method since it aims to critically analyze the influence of the factors that generate inequality between men and women in the criminal field, having as a theoretical-methodological basis Michel Foucault's approach to thinking, in the light of his theories on the role of institutions in the docility of bodies and on the connection between power relations and the domain of knowledge. It also finds theoretical contributions in the works of Heleieth Saffioti, regarding the issue of gender and its interrelation with other factors of discrimination, such as race and social class, in addition to Pierre Bourdieu's teachings on symbolic forces and on the naturalization of male domination. It concludes with the need for guidelines based on the expansion of the gender perspective for the deconstruction of symbolic violence against women, in the search for the promotion of the principle of equity